A Comparison between Coping Strategies of Bullied and Non-Bullied Adolescents - Hina Saleem Khan, Zainab Hussain Bhutto (Pakistan Journal of Clinical Psychology, 2020)
Objective: The research aimed to explore the coping strategies used by bullied and non-bullied adolescents. Design: Comparative research design. Place and Duration of the study: Participants were selected from seven private schools of Karachi city (Karachi, Federal and Cambridge systems). Study was conducted during January- June 2016. Subject and Method: Purposive sampling was used to select 110 participants, age ranges between 11-16 (M=14.54; SD=1.22) They were divided into groups of bullied and non-bullied using the mean scores of Multidimensional PeerVictimization Scale. Moreover, Brief COPE was used. Results and Conclusion: Significant difference was found in use of coping strategies, between bullied and non-bullied adolescents. Bullied adolescents were found to use both adaptive and maladaptive coping when dealing with victimization. Specific coping strategies used by them were self-distraction, denial, emotional support, behavioral disengagement, venting, humor, and acceptance and self-blame. Bullied individuals used both styles of coping more likely than non-bullied individuals.